Monetary policy and government debt dynamics without commitment - Dmitry Matveev (Bank of Canada, 2019)
I show that maturity considerations affect the optimal conduct of monetary and fiscal policy during a period of government debt reduction. I consider a New Keynesian model and study a dynamic game of monetary and fiscal policy authorities without commitment, characterizing the incentives that drive the choice of interest rate. The presence of longterm bonds makes government budgets less sensitive to changes in interest rates. As a result, a reduction of government debt induced by a lack of policy commitment is associated with tight monetary policy. Furthermore, the long maturity of bonds slows down the speed of debt reduction up to the rate consistent with existing empirical evidence on the persistence of government debt. Finally, the long maturity of bonds brings down the welfare loss associated with debt reduction.
Keywords: E52; E62; E63; 330; Monetary policy; Fiscal policy